Fluxos de capitais de portfólio para o Brasil no período 1995-2002: uma análise de vetores auto-regressivos e de causalidade - Veríssimo, Michele Polline (2004)
The present work analyses the dynamics of international capital flows to developing countries during the 1990s, and it develops an empirical investigation regarding foreign portfolio flows to Brazil for the period ífom 1995 to 2002. Other than this, it also examines the role of uncovered interest parity, country-risk and capital flows legislation to explain portfolio flows based on a vector autoregressive econometric analysis using impulse-response function, variance decomposition and Granger causality tests. In general, one can say that capital flows to Brazil have experienced a significant change over the last decade when portfolio flows represented the major source o f capital inflows for the first half o f the decade, which was not the case for the second half when foreign direct investments became the main source. The empirical analysis results corroborate the hypothesis of a low efflciency of capital measures expressed through a less restrictive legislation since they were not able to stimulate an increase in portfolio flows to Brazil during the period studied. On the other hand, the uncovered interest parity and the country-risk have played the main role in explaining portfolio flows, especially for total portfolio flows and federal funds. Finaíly, it is fair to say that capital flows to equity and derivative markets, due to their own peculiarities, have not been aífected in a significant way by the uncovered interest parity, country-risk or capital liberalization.